Imaging synaptic plasticity. - Padamsey, Z; Emptage, N (2011)
Over the past decade, the use and development of optical imaging techniques has advanced our understanding of synaptic plasticity by offering the spatial and temporal resolution necessary to examine long-term changes at individual synapses. Here, we review the use of these techniques in recent studies of synaptic plasticity and, in particular, long-term potentiation in the hippocampus.